Development of chemical kinetics based hydrogen HCCI combustion model for parametric investigation. (20th April 2016) - Sharma, Priybrat; Dhar, Atul
Abstract: Development of low pollution combustion technologies for internal combustion engines has become a major thrust area due to increase in air pollution from engine exhaust emissions. Homogeneous charge compression ignition (HCCI) combustion technology for internal combustion engines promises efficient combustion and cleaner emissions. HCCI engines can be run using multiple fuels such as gasoline, diesel, DME and hydrogen. Due to chemical kinetic nature of combustion in this engine, its combustion control is a major challenge. Using hydrogen as fuel can be a useful way to reduce emissions and improve combustion of HCCI engine. In the present work a stochastic multi zone chemical kinetics based model is developed to perform a parametric analysis on hydrogen HCCI engine. The model was validated against experimental results of HCCI engine run using hydrogen as fuel. Further, parametric studies were performed on the hydrogen HCCI engine using this model. Investigated parameters were equivalence ratio, intake temperature and charge quality. The parametric investigation is done to study the effect of these parameters on combustion and its control. The model is also used to predict the emissions of NOx at these varying parameters. Effectiveness of charge dilution using CO2 and H2 O in controlling the start of combustion has been examined. There was a noticeable agreement between the experimental results and simulated values. The parameters investigated show promising results, which can help in better control of ignition timings in hydrogen fuelled HCCI engine. Highlights: Fast zero dimensional model for hydrogen HCCI combustion. Parametric investigations of equivalence ratio, intake temperature on combustion rate. Charge dilution using CO2 and H2 O reduced combustion rate and NOx emissions. CO2 dilution was more effective than H2 O in controlling combustion phasing.